Reformulasi Proses Impeachment terhadap Presiden dan/atau Wakil Presiden yang Terbukti Melakukan Pelanggaran Sebagaimana Dimaksud dalam Pasal 7A UUD 1945 (The Reformulation of the Impeachment Process for the President and/or Vice President Found to Have Committed Violations as Referred to in Article 7A of the 1945 Constitution) - Habibi, Iskan; Nazri, Muhammad (UKInstitute, 2025)
Abstract. This study examines the reformulation of the impeachment process for the President and/or Vice President in Indonesia to ensure legal certainty and justice within the presidential system. The research is based on legal uncertainty in the impeachment mechanism, which still combines political and legal elements, where the decision of the Constitutional Court (MK) is not automatically binding on the People's Consultative Assembly (MPR). The objective of this study is to evaluate the impeachment mechanism in Indonesia, compare it with systems in other countries such as South Korea and Italy, and formulate an ideal concept to make the impeachment process more effective and aligned with the rule of law. The findings indicate that Indonesia's impeachment mechanism remains complex and tends to be more political than judicial. Therefore, a reformulation is necessary, including an amendment to Article 7B paragraph (5) of the 1945 Constitution, ensuring that Constitutional Court decisions are final and must be implemented by the MPR. With these reforms, the impeachment mechanism is expected to better reflect the principle of checks and balances and strengthen the rule of law within Indonesia's constitutional system. Abstrak. Penelitian ini membahas reformulasi proses Impeachment Presiden dan/atau Wakil Presiden di Indonesia dalam rangka memastikan kepastian hukum dan keadilan dalam sistem presidensial. Penelitian ini didasarkan pada ketidakpastian hukum dalam mekanisme impeachment yang masih menggabungkan unsur politik dan hukum, di mana putusan Mahkamah Konstitusi (MK) tidak serta-merta mengikat Majelis Permusyawaratan Rakyat (MPR). Tujuan penelitian adalah untuk mengevaluasi mekanisme Impeachment di Indonesia, membandingkannya dengan sistem di negara lain seperti Korea Selatan dan Italia, serta merumuskan konsepsi ideal agar proses Impeachment lebih efektif dan sesuai dengan prinsip negara hukum. Hasil penelitian menunjukkan bahwa mekanisme impeachment di Indonesia masih bersifat kompleks dan cenderung lebih politis dibandingkan yudisial, sehingga diperlukan reformulasi, termasuk amandemen Pasal 7B ayat (5) UUD 1945 agar putusan MK bersifat final dan wajib dilaksanakan oleh MPR. Dengan reformasi ini, diharapkan mekanisme impeachment dapat lebih mencerminkan prinsip checks and balances serta memperkuat supremasi hukum dalam sistem ketatanegaraan Indonesia.